2012
DOI: 10.1111/j.1753-5131.2012.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Economically important production relationships in channel catfish (Ictalurus punctatus) foodfish production

Abstract: The catfish industry (Ictalurus punctatus), the largest segment of aquaculture in the USA, has declined in the number of operations, total yield and sales in recent years. This has led to a call for innovations to improve production efficiency and to lower the cost of production. This paper reviewed the literature on management parameters that affect economically important production parameters under the control of an individual catfish farmer. Stocking density, size of fish at stocking, duration of culture, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Such lower stocking densities, combined with slightly smaller fingerlings, resulted in a low initial stocking biomass. Such lower stocking biomass (smaller fingerlings and lower stocking densities) has been shown to result in lower yields (Southworth et al ; Southworth et al ; Bastola and Engle ). A similar analysis by Johnson et al () suggested that catfish ponds with low stocking densities and high aeration rates resulted in greater production costs.…”
Section: Discussionmentioning
confidence: 99%
“…Such lower stocking densities, combined with slightly smaller fingerlings, resulted in a low initial stocking biomass. Such lower stocking biomass (smaller fingerlings and lower stocking densities) has been shown to result in lower yields (Southworth et al ; Southworth et al ; Bastola and Engle ). A similar analysis by Johnson et al () suggested that catfish ponds with low stocking densities and high aeration rates resulted in greater production costs.…”
Section: Discussionmentioning
confidence: 99%
“…This process often results in a wide range of production practices across farms at any given time. The US catfish production technologies have tended to become more intensive over time (Engle ) because the relatively high capital costs of US catfish production provide strong incentives to increase yields (Bastola and Engle ). However, farms with the greatest yields are not always the most profitable (Sarig ).…”
mentioning
confidence: 99%
“…Experimental designs seek to standardize and control as many factors as possible, including aeration, feeding, and predator control (Kumar & Engle, 2017a). The 10‐fold greater size of commercial ponds makes them more vulnerable to bird predation, although cormorants feed on 0.4‐ha research ponds as well, and reduces control over other factors (Engle et al, 2020; T. R. Hanson et al, 2020; Kumar, Hegde, et al, 2021) that result in higher and more variable FCR values when compared to results from research ponds (Bastola & Engle, 2012; Hegde, Kumar, Engle, Hanson, et al, 2022; Kumar, Engle, et al, 2021). Moreover, the very small 0.04–0.4‐ha research ponds typically are hand fed that is not possible on commercial‐scale ponds.…”
Section: Review Of Research Fcr Values and Factors That Affect Fcrmentioning
confidence: 99%